Peningkatan kemampuan guru dalam pembelajaran melalui supervisi observasi kelas di SDN 02 Talun Kabupaten Pekalongan - Sapto Yuwono (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to improve the ability of teachers in learning after the supervision technique of classroom observation was carried out at SD Negeri 02 Talun, Pekalongan Regency. This research was conducted at SD Negeri 02 Talun, Pekalongan Regency for 3 months with 2 cycles. The subjects of this study were class teachers from class I to class VI at SD Negeri 02 Talun. The object of research is the ability of teachers in teaching and learning activities and the implementation of classroom observation supervision techniques. The data that will be taken during the school action research is obtained by conducting observations, interviews, and documentation. By paying attention to the results of research and discussion of each cycle, it can be seen that there is an increase in the ability of teachers in learning planning, in managing teaching and learning activities and in evaluating teaching and learning activities. This proves that there is a positive influence from the implementation of classroom observation supervision techniques for improving teacher abilities and encouraging improvements in optimal learning. It is hoped that the results of this study will motivate the principal to carry out classroom observation supervision techniques as well as possible and position himself as a good role model and learning leader.